Understanding and Practice of Halal Labeling in A Multicultural Educational Environment: A Case Study at Songsermsasana School, Thailand - Ani Syah; Isra Hayati (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study investigates Muslim students’ understanding of halal labeling, the implementation of halal certification, and the factors influencing halal food management in a multicultural school setting in Southern Thailand. The study aims to examine how students understand halal concepts and certification, identify how halal food is managed in the school canteen, and explore factors shaping the implementation of halal assurance practices. A qualitative single-case study was conducted at Songsermsasana School, Songkhla. Data were collected through limited participant observation, semi-structured interviews with the school principal, administrative staff, canteen managers, and students, and document analysis. The findings show that students generally possessed a basic understanding of halal food, but their knowledge of halal certification, labeling, and the broader halal assurance system varied considerably. Halal food management in the school canteen was primarily implemented through informal routines and practical monitoring by canteen managers. However, during the study period, formal halal certification and labeling had not been integrated into documented management procedures. Several factors, including institutional policies, managerial practices, staff knowledge, and student awareness, influenced the implementation of halal food management. The study contributes empirical evidence on halal management practices in a multicultural educational environment and highlights the need for clearer institutional policies, standardized documentation, and stronger halal literacy among students and school personnel. These findings provide a practical reference for educational institutions seeking to strengthen transparent, systematic, and sustainable halal food assurance effectively.